Determinants of Mutual Fund Investment Returns: Evidence from Indian Retail Investors’ - Arunachalam, R.; Amudha, R. (International Journal of Economics and Financial Issues, 2025)
This study explores the relationships between socio-economic factors, other variables and the returns earned by retail investors from mutual fund investments. The analysis revealed significant determinants which captured different dimensions, such as socio-economic profile, investment affordability, information sources on financial topics, investment decisiveness, investment literacy, time horizon, risk level and investment goal, which are statistically tested and interpreted. The results of 822 responses collected from retail investors by adopting purposive sampling method highlighted the importance of enhancing investor awareness through financial literacy programs which can enable retail investors to make informed investment decisions and optimize their mutual fund returns. The findings of the study revealed that the key components like mutual fund literacy, exchange traded fund literacy, annual income, monthly investment percentage, holding period, investment experience and level of risk were the determinants of retail investors’ mutual fund investment returns.